THE CIRCUS AND CIRCUS’ PERFORMERS EXISTENCE IN THE GREATEST SHOWMAN MOVIE: A MARXISM STUDY - Evander Yosua Smith; Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2021)
ABSTRACT This study is held to: (1) To highlight the discrimination faced by P.T. Barnaum and his circus friends as lower class people, (2) To disclose the reason why the upper class people hated P.T. Barnaum’s circus, and (3) To find out the effects of discrimination experienced by PT Barnaum and his friends and how they overcame it using marxism theory by Karl Marx. This reasearch used qualitative methodology. The result of this study is that the discriminations faced by P.T Barnum and his circus friends were social class and physical appearance discrimination, upper class people hated P.T. Barnum’s circus because it was consi-dered fake and because of its performers’ appearances, P.T. Barnum and his friends experienced seclusion and inferiority complex. They overcame it by doing self-acceptance and looking for recognition. Keyword: Discrimination, popular culture, social categorization.